(untitled) (African Journal of Biomedical Research, 2022)
This study aims to contribute on improving the solid biomedical waste management in public health facilities in the municipality of Gulf 4 of Grand Lomé, by a descriptive method based on surveys and observations. 42.25% of the staff members were trained in biomedical waste management. Waste sorting was not effective in all units: 55.56% have already had at least one accident. These observations can be used to define a new strategy that will improve the management of solid biomedical waste in health facilities.